Membros: v. 4, n. 1 (2006) - ., .. (RENOTE, 2006)
Cleusa Maria Maximino Carvalho Alonso - UFSM Gilse Antoninha Morgental Falkembach - UNIFRA Julio Alberto Nitzke - SEAD/UFRGS Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Lucia Maria Martins Giraffa - Faculdade de Informática PUC/RS Magda Bercht - Instituto de Informática/UFRGS Mára Lúcia Fernandes Carneiro - UFRGS Marcelo Foohs - UERGS Marcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Maria Alice Gravina - Instituto de Matemática/UFRGS Marlise Geller - ULBRA Patrícia Alejandra Behar - Faculdade de Educação/UFRGS Ricardo Azambuja Silveira - UFPel Rosa Maria Vicari - Instituto de Informática/UFRGS Roseclea Medina - UFSM Sérgio Roberto Kieling Franco - PPGEDU/UFRGS Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS